Vulnerability to brown environmental problems within informal settlements in Seshego, Limpopo Province - Mahlakoana, Nicholene Ntlogeleng (University of Limpopo (Turfloop Campus), 2010)
Living in informal settlements is associated, theoretically, with the exposure and vulnerability to Brown Environmental Problems. Literature further stresses the association of informal settlements and poor living conditions by demonstrating that the establishment of informal settlements around the cities is intricately associated with poor living conditions that enforce circumstances of perpetual risk and high levels of vulnerability to Brown Environmental Problems. Overcrowding, poor service provision and heavy reliance on dirty fuels characterizes informal settlements and therefore link these settlements and environmental risks and hazards. The link between informal settlements and environmental risks and hazards is in return making people who live in these settlements vulnerable to, among other things, the Brown Environmental Problems, such as indoor pollution, dirty water, poor sanitation and poor waste management. It therefore became increasingly necessary to investigate the vulnerability to Brown Environmental Problems associated within these settlements. The investigation was done in Seshego, Zone 6, mostly known as Shushumela (Rainbow-Park). The study adopted a combination of the qualitative and quantitative approaches. The qualitative approach was used to describe the characteristics of the informal settlement, the types and origins of the Brown Environmental Problems, the living conditions within the settlement, and to detail the individual accounts of the informal settlements population’s opinions and experiences on their vulnerability. Additionally, quantitative approach was used to measure the demographic profile of the households within the settlements, to determine the population density in the settlements, the frequency of the households’ exposure to a variety of Brown Environmental Problems and the amount of time of exposure to dirty fuels, dirty water, and poor sanitation. The prevalence rate of the different types of the Brown Environmental Problems was also quantitatively constructed. The study compiled its conceptual framework by digesting and synthesising contributions from the system of ideas that involves the general assumption about the relationship between informal settlements living conditions and vulnerability of the populations therein to Brown Environmental Problems. Zone 6 is an informal settlement in Seshego, this settlement is also known as Rainbow Park-Shushumela. Like other informal settlements, Shushumela comprises of people who need a place to stay but unable to find one due to various reasons one of them being affordability issue. Shushumela informal settlement does not have basic services. Its residents stay in shacks and use their own ways to survive the situation of living without electricity, adequate sanitation and waste removal services. The residents are exposed to various Brown Environmental Problems such as indoor air pollution due the use of paraffin wood and coal, waterborne diseases and sanitation-borne diseases due to the limited access of water and use of pit latrines. The residents’ overall living conditions expose them to Brown Environmental Problems.
Thesis (M.Dev.) --University of Limpopo, 2010
Keywords: Informal settlements; Poor living conditions; 616.98071; Environmental problems; Squatter settlements; Rural health; Sanitation